2001
DOI: 10.1128/jcm.39.6.2294-2297.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Gram-Negative Bacteria on Central Venous Catheter Connectors: Effect of Conditioning Films in a Laboratory Model

Abstract: Human blood components have been shown to enhance biofilm formation by gram-positive bacteria. We investigated the effect of human blood on biofilm formation on the inner lumen of needleless central venous catheter connectors by several gram-negative bacteria, specifically Enterobacter cloacae, Pseudomonas aeruginosa, and Pantoea agglomerans. Results suggest that a conditioning film of blood components promotes biofilm formation by these organisms in an in vitro system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 15 publications
4
60
1
3
Order By: Relevance
“…As has been noted in the literature, conditioning films can render surfaces more favorable for bacterial adhesion (32,33). In our case, these conditioning films had the added effect of maintaining surface wetting.…”
Section: Discussionsupporting
confidence: 54%
“…As has been noted in the literature, conditioning films can render surfaces more favorable for bacterial adhesion (32,33). In our case, these conditioning films had the added effect of maintaining surface wetting.…”
Section: Discussionsupporting
confidence: 54%
“…We recently confirmed a direct link between Pseudomonas aeruginosa biofilm genetics and resistance to components of the human innate immune system (35). During this time, other papers have been published supporting our idea that P. aeruginosa and biofilms in general manipulate the immune system to their advantage (41,55,56). Most recently, O'Toole and colleagues demonstrated that P. aeruginosa biofilms growing on airway epithelial cells exhibited decreased virulence in the presence of the antibiotic tobramycin (1).…”
supporting
confidence: 53%
“…Murga et al investigated the effect of human blood on biofi lm formation on the inner lumen of needleless central venous catheter connectors by Enterobacter cloacae, P. aeruginosa , and Pantoea agglomerans ; and found that conditioning with whole blood resulted in signifi cantly higher viable colony counts than non-conditioned controls (Murga et al 2001 ). Another study examined gene expression of a single S. aureus USA300 isolate in response to human blood, and demonstrated that whole blood induced greater expression of fi bronectin binding protein and extracellular fi brinogen binding protein, which could potentially impact biofi lm formation (Malachowa et al 2011 ).…”
Section: Infl Uence Of Host Factors On Biofi Lm Formationmentioning
confidence: 98%